Kepemimpinan Kyai dalam Upaya Menciptakan Kemandirian Santri - Chusnul Chotimah (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2016)
Leadership in the effort to create self-sufficiency students, boarding school in order to determine the independence of students in development and are able to form and nurture students are effective but are able to create an independent and professional students. Tradition cottage for 24 hours to supervision and control of a clerics is a vital tool that can influence and shape its students in self-reliance as a leader clerics have a very important role in the discipline of students. This is because the clerics as a figure that can be used as a mediator, as well as a dynamic factor for the community motovator lead